On-Orbit Thermal Design and Validation of 1 U Standardized CubeSat of STEP Cube Lab - Soo-Jin Kang; Hyun-Ung Oh (International Journal of Aerospace Engineering, 2016)
The Cube Laboratory for Space Technology Experimental Projects (STEP Cube Lab) is a cube satellite (CubeSat) classified as a pico-class satellite of 1 U (unit) size. Its main mission objective is to exploit core space technologies researched by domestic universities and verify the effectiveness of these technologies through on-orbit tests using the CubeSat. To guarantee a successful mission under extreme space thermal environments, proper thermal design is important. This paper describes the development process undertaken in the thermal design of the STEP Cube Lab, based on a passive approach, and its validation test. The system functionality and thermal design were verified through thermal vacuum and thermal balance tests under space simulated thermal vacuum environment condition. Finally, the orbital temperature of each component was predicted using a highly reliable correlated thermal mathematical model of the CubeSat obtained from the thermal balance test.